Isolation of endophytic bacteria from soursop leaf (Annona muricata) and secondary antioxidant metabolite activity testing - Sarjono, Purbowatiningrum Ria (Universitas Negeri Yogyakarta, 2023)
Free radicals are molecules or molecular fragments that contain unpaired electrons in the valence shell. To achieve stability, free radical molecules will react with surrounding molecules. Free radical molecules in the body take place continuously and are difficult to stop, this can cause diseases such as premature aging and cancer. Therefore, the required compound has antioxidant activity to stop it. One of the antioxidant compounds can be obtained by utilizing secondary metabolites of Soursop leaf endophytic bacteria (Annona muricata). Soursop leaf endophytic bacteria isolates have been obtained which have the form of diplobacillus and include gram-positive bacteria. The activity was carried out using the DPPH method and obtained IC50 of 278.27 ppm at the 22nd hour and 61.942 ppm at the 24th hour. The total phenolic obtained at the 22nd hour was 79 mgek of gallic acid/g while at the 24th hour it was 34 mgek of gallic acid/g. Secondary metabolites of soursop leaf endophytic bacteria produce secondary metabolites in the form of alkaloids and terpenoids.